2021
DOI: 10.5194/acp-21-10179-2021
|View full text |Cite
|
Sign up to set email alerts
|

On the contribution of fast and slow responses to precipitation changes caused by aerosol perturbations

Abstract: Abstract. Changes in global-mean precipitation are strongly constrained by global radiative cooling, while regional rainfall changes are less constrained because energy can be transported. Absorbing and non-absorbing aerosols have different effects on both global-mean and regional precipitation, due to the distinct effects on energetics. This study analyses the precipitation responses to large perturbations in black carbon (BC) and sulfate (SUL) by examining the changes in atmospheric energy budget terms on gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…globally distributed vs. regionally confined perturbations), they also find that the total precipitation response to both global BC and global sulphate are dominated by the fast response over parts of South Asia and most of the African continent. High latitude precipitation responses to these two forcers, meanwhile, are dominated by the slow precipitation response in the multi-model simulations (Samset et al, 2016), though individual models show conflicting results (Zhang et al, 2021). Similar multi-model simulations with regional idealized aerosol emissions over Asia and Europe , however, also showed a strong local fast precipitation response to Asian aerosols and almost no fast precipitation response to European aerosols.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…globally distributed vs. regionally confined perturbations), they also find that the total precipitation response to both global BC and global sulphate are dominated by the fast response over parts of South Asia and most of the African continent. High latitude precipitation responses to these two forcers, meanwhile, are dominated by the slow precipitation response in the multi-model simulations (Samset et al, 2016), though individual models show conflicting results (Zhang et al, 2021). Similar multi-model simulations with regional idealized aerosol emissions over Asia and Europe , however, also showed a strong local fast precipitation response to Asian aerosols and almost no fast precipitation response to European aerosols.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, this signal may be largely dependent on parameterization approach. Applying well-established energetic analysis approaches (Dagan et al, 2021;Ming et al, 2010;Zhang et al, 2021) to more realistic aerosol perturbations in combination with moisture tracking algorithms (Mei et al, 2015) that allow better characterization of precipitation sources could help further clarify the potential role of local versus large-scale precipitation controls in determining the emergence of in-situ precipitation responses to regional aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…These results with the time-evolving variables do not clarify how representative pre-industrial to 1975 aerosol ERF is of transient aerosol radiative effects in the coupled simulations. Secondly, studies have shown that the slow precipitation response to aerosol forcing is a more effective driver of ITCZ shifts than the fast precipitation response (Voigt et al, 2017;Zhang et al, 2021). By definition aerosol ERF does not quantity the climate response to aerosol-mediated surface temperature changes, and hence alongside the time-evolving variables related to aerosol radiative effects may not be a useful proxy for aerosol-driven slow precipitation changes (which occur through surface temperature change).…”
Section: Potential Factors Obscuring a Relationship Between Tropical ...mentioning
confidence: 99%
“…The response of precipitation to anthropogenic aerosol is commonly decomposed into 'fast' and 'slow' contributions (Samset et al 2016;Voigt et al 2017;Zhang et al 2021). Fast responses occur in the first days or months following the perturbation and are independent of sea-surface temperature (SST) changes (and so are efficiently studied using fixed-SST simulations).…”
Section: Introductionmentioning
confidence: 99%